Landscape characteristics and its relationships with the diversity and structure of riparian vegetation of southeastern Mexico - Moreno-Jiménez, Victorio; Gama-Campillo, Lilia María; Romero-García, Alejandro; Ochoa-Gaona, Susana; Contreras-Sánchez, Wilfrido Miguel; Jiménez-Pérez, Nelly del Carmen; Mata-Zayas, Ena Edith (Instituto de Ecología, A.C., 2019)
Background and Aims: Land use change generated by human activities has fragmented riparian corridors causing changes in the diversity and structure of its vegetation. The objective of this study was to compare the diversity, structure and floristic similarity in five sites of the Tacotalpa River, Tabasco, Mexico, related to vegetation variables with landscape metrics.Methods: Sampling was performed at five sites of the Tacotalpa River: Tapijulapa (s1), Arroyo Chispa (s2), Nuevo Madero (s3), Mexiquito (s4) and Oxolotán (s5). At each site, 20 sampling units of 10 × 10 m were established. Trees and shrubs with a DBH ≥1 cm were counted. The diversity and structure were compared with a one-way ANOVA. The floristic similarity between sites was compared with a Bray-Curtis cluster, Pearson correlation and PCA between vegetation variables and landscape metrics, using PAST and SPSS.Key results: There were 2589 individuals in 38 families, 92 genera and 119 species. The diversity 0D of s2 was statistically lower than s1 and s3, while 1D was similar in the five sites. The tree density of s1 was significantly greater than in s2, s3 and s5. The averages of DHB and height of s1 were low, showing significance with s2 (p <0.05). The floristic similarity ranged from 0.41 to 0.58. Order 0D diversity, shrub species and tree density correlated positively with some of the landscape metrics. The 1D diversity and tree species correlated positively with the paved road distance, and height with the dirt road.Conclusions: The differences between the sites suggest that there are different levels of disturbance along the Tacotalpa River. Positive correlations between vegetation variables and landscape metrics indicate that infrastructures near the river modify the diversity and structure of the riparian vegetation.